2019
DOI: 10.1002/1873-3468.13624
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional downregulation of miR‐127‐3p by CTCF promotes prostate cancer bone metastasis by targeting PSMB5

Abstract: Prostate cancer (PCa) is one of the most common cancers in males and particularly tends to metastasize to bone. Currently, metastatic bone disease is incurable, and new therapies need to be developed. Our study aims to determine the role of miR‐127‐3p in PCa metastasis to bone. The results demonstrate that miR‐127‐3p is markedly reduced in bone metastasis‐positive PCa tissues relative to that in bone metastasis‐negative PCa tissues. Furthermore, overexpressing miR‐127‐3p inhibits PCa cell invasion and migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…Moreover, the proteasome may be involved in the development of cancer metastasis (53,54). Fan et al reported that miR-127-3p could target PSMB5 to inhibit the invasion and migration of PCa cells (53). Consistent with our results, several studies found that the proteasome can be detected in exosomes (42,55,56).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the proteasome may be involved in the development of cancer metastasis (53,54). Fan et al reported that miR-127-3p could target PSMB5 to inhibit the invasion and migration of PCa cells (53). Consistent with our results, several studies found that the proteasome can be detected in exosomes (42,55,56).…”
Section: Discussionsupporting
confidence: 91%
“…All those miRNAs exhibited high discriminatory power (AUC above 0.85). MiR-127-3p has been shown to exhibit a tumor suppressor function in osteosarcoma [52], giant cell tumors of bone [53], prostate cancer bone metastasis [54], epithelial ovarian cancer [55], and glioblastoma [56]. miR-409-3p inhibits cell proliferation and invasion of osteosarcoma [57], tongue squamous cell carcinoma [58], breast cancer [59], and prostate cancer [60].…”
Section: Discussionmentioning
confidence: 99%
“…Ion AmpliSeq Comprehensive Cancer Panel (ThermoFisher Scientific, Waltham, MA, United States) libraries were prepared from DNA samples for the analysis of the coding regions of 409 oncogenes and tumor suppressor genes by sequencing on an Ion Proton sequencer with the Ion PI Hi-Q Chef Kit, loading four samples onto an Ion PI Chip, as described previously [54].…”
Section: Profiling Of Dna Variantsmentioning
confidence: 99%
“…Siu et al demonstrated that KLF4 functions as a transcription factor to activate the AR-miR-1 signaling pathway to constrain the tumor-suppressive role of miR-1 [50]. CTCF, a downstream transcription activator of Smad and Myc signaling, contributes to slowing down metastasis in PCa through directly interacting with the miR-127-3p promoter, in which the downregulation of miR-127-3p accompanies proteasome subunit beta type-5 (PSMB5) elevation and subsequently leads to the activation of BM [55][56][57]. All of the above research draws a large picture of the regulatory mechanism of BM in PCa cells, and Figure 1 summarizes these signaling cascades.…”
Section: Other Minor Emt Contributorsmentioning
confidence: 99%